Язык мой- враг мой: [роман] / Варвара Клюева - Клюева Варвара (Ирония+детектив=, 2001)
Экземпляры: ф.2 (20210416) / Инвентарный номер: 61408 / Цена: / Авт.знак: К 52 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44